Stand-alone and hybrid wind energy systems : technology, energy storage and applications - Kaldellis, J. K. ([S.l.] : CRC Press, 2010)
Wind power generation is fast becoming one of the leading renewable energy sources worldwide. Reliability of power supply is one of the main issues for wind energy systems, and so improved stand-alone and hybrid wind energy systems are being developed, incorporating advanced energy storage and grid integration systems, in order to increase power generation rates and to provide secure power supply to the end user. This book provides a comprehensive reference on the development of both stand-alone and hybrid wind energy systems, as well as energy storage systems and overall systems integration with local grids. Chapters cover the design/construction, modeling/simulation, monitoring/control, and optimization of stand-alone and hybrid wind energy technologies, reviewing their current state and future development. Further to this, many of the energy storage and distribution systems covered in the book are also applicable to other renewable energy generation technologies.